Coastal Protection Strategy And Its Impact On Abrasion Disaster Mitigation In The Wonokerto Coastal Area Pekalongan City - Hanung Garnish Aulia; Aditya Saputra (Dinasti International Journal of Education Management And Social Science, 2024)
This study aims to identify what are the coastal protection strategies and identify the impacts of abrasion disasters on the region. In addition, this study also wants to ensure that mitigation efforts not only focus on physical protection, but also consider the sustainability of ecosystems and the well-being of coastal communities. In addition, this study also wants to ensure that mitigation efforts not only focus on physical protection, but also consider the sustainability of ecosystems and the well-being of coastal communities. The research method used is literature study and secondary data analysis related to coastal protection strategies that have been implemented and their impact on abrasion mitigation. The results of the study show that the implementation of coastal protection strategies such as the construction of breakwaters, sea embankments, mangrove management, sand management, by adding sand to eroded beaches, implementing integrated management of coastal areas has had a positive impact on abrasion disaster mitigation in the region. However, challenges such as climate change and ecological imbalances need to continue to be considered in designing sustainable coastal protection strategies in the future. In conclusion, this study provides useful insights for policymakers and practitioners related to abrasion disaster mitigation efforts in the coastal area of Wonokerto, Pekalongan.